The working disadvantaged: the role of age, job tenure and disability in precarious work - Arif Jetha; Kathleen A. Martin Ginis; Selahadin Ibrahim; Monique A. M. Gignac (BMC, 2020)
Abstract Background Precarious work is an increasingly common characteristic of industrialized labor markets that can widen health inequities, especially among disadvantaged workforce segments. Study objectives are to compare precarious employment in workers with and without disabilities, and to examine the modifying effect of disability in the relationships between age, job tenure and precarious work. Methods Employed Canadians with (n = 901) and without disabilities (n = 901) were surveyed on exposure to precarious working conditions. Information on age and job tenure were collected from respondents along with sociodemographic, health and work context details. Multivariable logistic models examined the association between disability and precarious work. Also, multigroup probit models examined precarious work for young (18-35 yrs), middle-aged (36-50 yrs) and older adults (> 50 yrs) and job tenure and was stratified by participants with and without disabilities. Results Almost equal proportions of young, middle-aged and older participants were recruited. Mean job tenure of participants was 9.5 years (SD = 9.0). Close to one-third of participants reported working precariously. At the multivariable level, a disability was not associated with working precariously. However, multigroup modelling indicated that disability was a significant effect-modifier. Older adults with a disability had a 1.88 times greater odds of reporting precarious work when compared to young adults (OR = 1.88, 95%CI 1.19, 2.98). When reporting a disability, longer job tenure was related to a 0.95 times lower odds of precarious work (OR = 0.95 95%CI 0.93, 0.98). The relationship between age and job tenure was not significant for those not reporting a disability. Discussion Precarious work has the potential to affect workers with and without disabilities. For those with a disability, being an older adult and/or a new worker can contribute to a greater likelihood of being employed precariously. Policies and programs can be recommended to address precarious working conditions and related health inequities for people with disabilities based on life and career phase.